Determinants of Student Persistence in Completing BS Agriculture Degrees in the University of the Philippines - Ruth A. Ortega-Dela Cruz; Maria Ana T. Quimbo (Journal of International Agricultural and Extension Education, 2018)
The study used descriptive research design to identify factors that explain persistence of BS Agriculture (BSA) students in the University of the Philippines Los Baños during their first year of college as they moved on to the next year level towards degree completion. In addition to self-administered questionnaire, Key Informant interviews were also conducted. Findings reveal that institution-related factor particularly the institution’s commitment to academic excellence constitutes most to the experiences of agriculture students. Analysis of Variance reveals a significant difference in the persistence of BS Agriculture students across year levels. The results of the study point out that, as per responses of the students as well as the faculty and administrators interviewed, the University has not gone far enough to ensure that BSA students are supported in an efficient manner. The University of the Philippines, being the National University has much opportunity to make positive changes in persistence of these special populations of agriculture students. Thus, it needs to take steps toward making more of a commitment to student success
Keywords: agriculture education; degree completion; determinants; persistence; Philippines